The effect of selected herb extracts on oxidative stability of vegetable oils - Soldo, Barbara; Anđelić, Ivana; Nikolov, Nikolina; Skroza, Danijela; Šimat, Vida; Ljubenkov, Ivica; Generalić Mekinić, Ivana (2019)
The aim of this study was to investigate the effect of different herb extracts on the oxidative stability of hemp, flax, sesame and sunflower seed oils by means of Rancimat test. The dominant phenolic acids in herb extracts were detected by HPLC, while fatty acid profiles of oils, before and after oxidation, were determined by GC-FID. As expected, autoxidation increased the content of saturated fatty acids. The sesame oil showed the longest oxidative stability (3.43 h), while the shortest induction period was obtained for the flax oil. Lemon balm and oregano extracts accelerated the oxidation of hemp and flax oil, while in all other cases the addition of extracts had a positive effect on oil oxidative stability. The best results were obtained for lemon balm extract added to sesame and sunflower oil which resulted with OSI values of 1.33 and 1.48, respectively, while extremely prooxidative activity was obtained for lemon balm extract added to the hemp oil.
Bibliografija: 26 jed.
Abstract.
Keywords: Biljna ulja -- Oksidacijska stabilnost -- Molekularna dinamika -- Konformacijska analiza